Value of plasmid profiling, ribotyping, and detection of IS200 for tracing avian isolates of Salmonella typhimurium and S. enteritidis. - Millemann, Y (1995)
Seventy selected strains of Salmonella typhimurium and S. enteritidis isolated from related poultry flocks in three independent geographical areas were characterized by phenotypic and genotypic methods to compare the usefulness of the methods in epidemiological studies. The 56 S. typhimurium isolates were poorly discriminated by their biotypes, resistance patterns, and plasmid profiles. Nine different ribotypes were obtained after DNA digestion by BglII, PvuII, and SmaI. Seven IS200 types, characterized by six to nine copies of IS200 on the chromosome, were detected after digestion of genomic DNA by PstI. These studies resulted in the definition of 15 clonal lineages distributed in three clusters. The 14 S. enteritidis strains were not discriminated either by ribotyping or by detection of IS200 (IS200 typing), but were separated on the basis of antibiotic resistance and plasmid profiling. The stability of the insertion sequence type was confirmed by inoculation of an S. typhimurium strain to axenic chickens reared for 15 weeks in sterile isolators.